E-tools for hospital management: An overview of smartphone applications for health professionals. (April 2019) - Olivero, E.; Bert, F.; Thomas, R.; Scarmozzino, A.; Raciti, I.M.; Gualano, M.R.; Siliquini, R.
Highlights: Most of the applications were designed for health operators and patients' management. The large majority of apps counted less than 1000 downloads. Most of them were in English and free to download. Abstract: Background: Commonly, management of the main hospital activities is organized by different software packages that run on desktop computers, which may not always allow fast and practical use by health operators. This problem could be alleviated by combining these software packages with mobile health. The aim of this study is to provide an overview of smartphone and tablet applications used for hospital management and administration in order to evaluate their features and analyze them according to their content, number of downloads and field of application. Methods: Researchers performed the survey on the two main application stores available on the Internet: iTunes for Apple devices and Google Play for Android devices. Using specific keywords, 47 apps that met the inclusion criteria were identified. Results: Most of the applications were designed for health operators and patient management (76.6%); 12.8% of the apps were focused on the organization and setting of hospital resources, and 10.6% of the apps could help hospital administrators perform self-evaluations of their structures, processes and outcomes. The large majority of apps (80.7%) counted less than 1000 downloads. Most of them (87.5%) were in English and free to download (93.6%). Discussion: The results of the first attempt to provide an overview of this emerging topic showed that, despite the existence of several applications for hospital management purposes, these tools appear to be not very widespread. In our opinion, there is a strong need to further assess the quality of these applications; thus, it may be worth continuing to monitor this field in order to analyze eventual improvements in the design and distribution of these apps.